'Is this normal?' The role of category predicates in constructing mental illness online. Issue 4 (11th June 2013) - Giles, David C.; Newbold, Julie
Abstract One of their functions of online mental health communities is the construction of coherent identities for their members based on the various characteristics of different mental health conditions. This paper contains microanalyses of 2 message threads on mental health discussion forums—one concerning depression and the other 'emetophobia' (fear of being sick)—which illustrate some of the discursive functions of such forums. Conversation analytic techniques are employed, such as the use of second stories for social support purposes, and the generation of category predicates for building up a set of activities that constitute 'normality' in this context. It is argued that these socially situated practices constitute a more important function of online support groups than the mere dissemination of 'advice'.